Simple DC-Link Voltage Balancing Approach for Cascaded H-Bridge Rectifier with Asymmetric Parameters of Independent DC Loads - Jin Zhu (Energies, 2019)
CHB is a suitable type of topology for synchronous rectifier application which has two or more independent DC loads. Focusing on the individual DC-link capacitor voltage balancing problems caused by asymmetric parameters of independent DC loads, this paper developed a new dual modulation signals based phase disposition pulse width modulation (PD-PWM) strategy using dynamic carrier bias allocation method. Its main idea is to allocate the bias of the carrier wave dynamically according to the balance situation of the system. Compared with the traditional modulation strategies, this method is more easily to be realized and has much stronger dynamic regulation ability. This modulation strategy is widely applicable to various types of CHB structures. A detailed analysis of the DC-link capacitor charge-discharge profile is performed, and an operation condition based dynamic bias allocation method is described using the cascaded H-bridge rectifier (CHBR) structure of five sub-modules as an example. A simulation model and an experiment platform are developed, and the feasibility and effectiveness of the modulation strategy are verified by simulation and experiment results.